2011
DOI: 10.1002/maco.201005983
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion at the urea injection in SCR‐system during component test

Abstract: The corrosion behaviour of the austenitic stainless steels 304L and 904L was investigated after component testing in diesel exhaust urea environment. Cross‐sectional analyses and depth profiling of corrosion products were performed with Auger electron spectroscopy (AES) and X‐ray photoelectron spectroscopy (XPS). The samples of both materials displayed high amounts of silicon oxide on their surfaces, though this did not appear to have an active role in the corrosion. The higher alloyed 904L exhibited only smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…For 304L-L bcc formed during oxidation. The narrow peaks at 550 and 600°C could be consistent with a phase transformation S  bcc + fcc + CrN (1) This confirms that the S phase is less stable than austenite since, in comparison, the minor amount of bcc in as received 304L did not increase during oxidation. Several factors could contribute to the broad peak for bcc at 450°C.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…For 304L-L bcc formed during oxidation. The narrow peaks at 550 and 600°C could be consistent with a phase transformation S  bcc + fcc + CrN (1) This confirms that the S phase is less stable than austenite since, in comparison, the minor amount of bcc in as received 304L did not increase during oxidation. Several factors could contribute to the broad peak for bcc at 450°C.…”
Section: Discussionsupporting
confidence: 52%
“…The first nitriding condition, H, resulted in N concentrations almost twice as high as those on corroded components in 904L [1]. Moreover, for 904L a multitude of cracks formed both through the layer thickness and in parallel with the surface.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, more generally, it is concluded that the cracking and fracturing of metal is related to urea decomposition products and intergranular attack [2,4,[14][15][16][17][18]. By many scientists, an intergranular corrosion mechanism, sometimes attributed to chromium depletion, and nitride precipitation at grain boundaries, and sometimes without any indication of decrease or increase in the amount of chromium at grain boundaries, was described [4,19,20].…”
Section: Introductionmentioning
confidence: 99%